2020
DOI: 10.5093/ejpalc2020a9
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Personality Characteristics of Juvenile Offenders in a Detention Centre regarding Recidivism Risk

Abstract: This study analyses the psychosocial characteristics based on recidivism risk of juvenile offenders in conditions of internment. A sample of 102 juvenile offenders (92 male, 10 female) who were serving sentences in the only detention centre in Navarra (Spain) was used. Data on sociodemographic and psychosocial characteristics as well as features related to recidivism risk were collected through the Youth Level of Service/Case Management Inventory (YLS/CMI) and data on personality characteristics were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
6
0
1
Order By: Relevance
“…The results have confirmed a significant increase in the use of avoidance strategies in a pandemic situation, specifically Cognitive avoidance (cognitive attempts to avoid thinking realistically about a problem), Acceptance or resignation (cognitive attempts to react to the problem by accepting it), Seeking alternative rewards (behavioral attempts to get involved in substitute activities and create new sources of satisfaction) and Emotional discharge (behavioral attempts to reduce tension by expressing negative feelings), in line with the literature that has pointed out the cognitive avoidance (Babore et al, 2020;Herrero et al, 2019;Vagni et al, 2020), and the emotional discharge to reduce tension through the expression of negative feelings, as the most likely resources for coping with an epidemic event (Teasdale et al, 2012). These avoidance strategies are not only ineffective, but also facilitate the appearance of psychological damage and incompetence to solve problems (APA, 2013;Brooks et al, 2019;Cacho et al, 2020;Mayorga et al, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…The results have confirmed a significant increase in the use of avoidance strategies in a pandemic situation, specifically Cognitive avoidance (cognitive attempts to avoid thinking realistically about a problem), Acceptance or resignation (cognitive attempts to react to the problem by accepting it), Seeking alternative rewards (behavioral attempts to get involved in substitute activities and create new sources of satisfaction) and Emotional discharge (behavioral attempts to reduce tension by expressing negative feelings), in line with the literature that has pointed out the cognitive avoidance (Babore et al, 2020;Herrero et al, 2019;Vagni et al, 2020), and the emotional discharge to reduce tension through the expression of negative feelings, as the most likely resources for coping with an epidemic event (Teasdale et al, 2012). These avoidance strategies are not only ineffective, but also facilitate the appearance of psychological damage and incompetence to solve problems (APA, 2013;Brooks et al, 2019;Cacho et al, 2020;Mayorga et al, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…Psychopathy has been characterized as a personality construct that combines egocentricity, callousness, failure to form close emotional bonds, proneness to low anxiety, lack of remorse, superficial charm, dishonesty, and impulsive behaviour (Cacho et al, 2020;Forth et al, 1996;Hare, 1991;Hare & Neumann, 2008). Research has shown that many of these dimensions could be predictors of criminal behaviour (Frick et al, 2003;Garofalo et al, 2020;Piatigorsky & Hinshaw, 2004).…”
Section: Psychopathic Traitsmentioning
confidence: 99%
“…The present study aimed to expand this framework by adapting and validating a staff version of the PLANEA Independent Life Skills Assessment tools and narrowing the gap in knowledge on the effectiveness of transitional support interventions for young people in care and their perceptions of independent life skills. This is especially pronounced in the Spanish context where, in contrast with the consolidated body of evidence-based practice, programs and assessment tools available in other related areas such as family intervention (De Paul et al, 2015;Rodrigo, 2016), intervention with juvenile offenders (Cacho et al, 2020), or quality evaluation in residential child care (Pérez-García et al, 2019), the specific evaluation of transitional support services is still recent and has limited its scope to gather young people's and workers' views and satisfaction (Goig & Martínez, 2019;Sevillano-Monje et al, 2021). The results of the CFAs performed in the staff versions of the three instruments studied allowed us to confirm the same internal structure found in the young people versions: three first-order factors and one second-order factor (Independent Life Skills) in the case of PLANEA-S, unidimensionality for its short version PLANEA-9-S, and two first-order factors correlated between them, showing a global score (Personal Autonomy) for PLANEA-T-S (García-Alba et al, 2021).…”
Section: Discussionmentioning
confidence: 99%